2011
DOI: 10.1039/c1cp21691k
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tunneling on hydrogen-migration of the n-propylperoxy radical

Abstract: The kinetics of three unimolecular reactions of the n-propylperoxy radical were studied by canonical variational transition state theory and multidimensional small curvature tunneling (SCT). The reactions studied were 1,5 and 1,4 H-migration, and HO(2) elimination. Benchmark calculations were carried out at the CCSD(T) level in order to determine which density functional to use for SCT calculations for each reaction. For 1,5 and 1,4 H-migration, and HO(2) elimination, the M05-2X, B3LYP and B1B95 functionals, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
92
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 65 publications
6
92
0
Order By: Relevance
“…The corresponding rate constant using Eckart tunneling correction is 8.48 × 10 9 M −1 s −1 , which is 30.5% higher than the experimental value. It is reported that the Eckart method is often found to overestimate the tunneling corrections . The calculated rate constant using Wigner's method is in a good agreement with the experimental value.…”
Section: Resultssupporting
confidence: 61%
“…The corresponding rate constant using Eckart tunneling correction is 8.48 × 10 9 M −1 s −1 , which is 30.5% higher than the experimental value. It is reported that the Eckart method is often found to overestimate the tunneling corrections . The calculated rate constant using Wigner's method is in a good agreement with the experimental value.…”
Section: Resultssupporting
confidence: 61%
“…As is typical, is much broader than the Eckart potential. 8,30 This leads to the expectation that  ZCT will be much smaller than  Eckart . Corner-cutting will tend to increase multi-dimensional tunneling coefficients above  ZCT .…”
Section: Resultsmentioning
confidence: 99%
“…9 The presence of the -OOH group lowers the barrier to 1,5 Hshift by ~4 kcal/mol as compared to that in 1-propylperoxy radical. 8,9 As indicated in Reaction 1, the radical product of this 1,5 H-migration will fall apart to hydroxyl radical plus a ketohydroperoxide. This radical product is absolutely unstable or only slightly metastable with respect to O-O scission.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The third part of the protocol involves the calculation of the κ(T) tunneling correction, obtained through the Eckart method, which is widely used in atmospheric chemistry studies . To calculate this correction, we started by selecting the TS conformer with the lowest ZPE‐corrected energy and calculating the IRC in both reactants and products direction at the M08‐HX/pcseg‐1 level of theory.…”
Section: Methodsmentioning
confidence: 99%